Erratum to: Impact of extreme magnetic fields on the QCD topological susceptibility in the vicinity of the crossover region - B. B. Brandt; G. Endrődi; J. J. Hernández Hernández; G. Markó (Journal of High Energy Physics)
A correction to this paper has been published: https://doi.org/10.1007/JHEP12(2024)228